ANALISIS PENGGUNAAN MEDIA GAMBAR FLASHCARD TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DALAM MATERI “ AKU DAN LINGKUNGAN SEKITARKU” DI KELAS III SD 060925 MEDAN - Maulida Syakira Nasution; Safrida Napitupulu; Rosmawati Harahap; Nila Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to determine the influence, increase in student learning interest and the effectiveness of the use of flashcard image media on the understanding of grade III SD students in studying the material "Me and My Surrounding Environment. This research method uses a qualitative descriptive method. The type of research design used is qualitative research. These participants will be seen from how the development of students in the subject of science. The results of this study are that the use of flashcard image media has a positive effect on student learning outcomes. This is evidenced by questionnaire data which shows that the majority of students gave responses in the categories "YES" and "NO". This media helps students understand the material more easily, interestingly, and enjoyably. Flashcards help visualize environmental concepts in concrete terms. Students recognize their home, school, and public environments more quickly through the images provided, so they can understand the material better. Flashcard image media increases student participation and activeness in learning. Students appear more enthusiastic, active in discussions, and are able to work together with their group members. This makes the learning process less boring and more meaningful. Interviews with teachers support the qualitative data obtained. Teachers stated that flashcard media is very helpful in delivering science and natural sciences material, and is able to increase students' enthusiasm for learning, especially for students who were previously passive.